2016
DOI: 10.1038/srep28256
|View full text |Cite
|
Sign up to set email alerts
|

A series of compact rejection filters based on the interaction between spoof SPPs and CSRRs

Abstract: We propose a method to synthesize several band-rejection filters by etching split-ring resonators (SRRs) on the transmission line for spoof surface plasmon polaritons (SPPs), which is made of double-side or single-side corrugated metal strips. From dispersion relations, the corrugated strips can support spoof SPP modes when the operating frequency is less than the cutoff frequency. The electric field component perpendicular to the strip surface of the SPP modes can excite the complementary SRRs (CSRRs), leadin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 33 publications
0
41
0
Order By: Relevance
“…In order to remove harmonics in electronic devices and communication systems, the filters based on spoof SPPs are widely stud-ied, particularly the passive devices including the band-stop filters and the band-pass filters. In terms of the band-stop filter, changing the several groove structures of spoof SPP TL or utilizing the resonant metamaterials as well prevents the EM wave transmission in specific frequency ranges [59][60][61][65][66][67][68][69]. Ref.…”
Section: Filters Based On Spoof Sppsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to remove harmonics in electronic devices and communication systems, the filters based on spoof SPPs are widely stud-ied, particularly the passive devices including the band-stop filters and the band-pass filters. In terms of the band-stop filter, changing the several groove structures of spoof SPP TL or utilizing the resonant metamaterials as well prevents the EM wave transmission in specific frequency ranges [59][60][61][65][66][67][68][69]. Ref.…”
Section: Filters Based On Spoof Sppsmentioning
confidence: 99%
“…Fig. 4 shows the structure of band-rejection filter by etching split-ring resonators (SRRs) on spoof SPP transmission line [68]. The complementary SRRs (CSRRs) lead to resonant modes and further prevent the SPP propagation.…”
Section: Filters Based On Spoof Sppsmentioning
confidence: 99%
“…Researches have demonstrated that the upper passband cutoff frequencies of these filters can be independently adjusted by the geometrical parameters of SSPPs waveguides. In addition, in order to realize band-rejection responses for practical applications, series of band-stop filters are proposed by etching split-ring resonators (SRRs) [28] or complementary SRRs (CSRRs) [29] in the traditional SSPPs structures with corrugated strips. It differs from the bandpass filters based on the magnetic coupling between planar Goubau line and resonators [30], [31], since the resonant modes of SRRs or CSRRs are excited effectively by the electric field components of SSPPs modes perpendicular to the strip surface, leading to a stopband near the resonant frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…SSPPs possess excellent properties of stronger field confinement and enhancement capability, dispersion control capability than other planar slow wave structures, and sub‐wavelength size. Hence, it can be widely applied to many radio frequency circuits and systems, such as low‐crosstalk line, filters, power divider, antennas, sensor, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…So far, many researches on ultrathin SSPPs band‐stop filter have been reported. Most of these works have utilized extra resonant structures on the center of the strip even the back of the substrate to realize the stop band, such as the split‐ring resonators or other metamaterial particles . However, these band‐stop filters cannot control the stop band spectrum or bandwidth independently.…”
Section: Introductionmentioning
confidence: 99%